Investigation of Morphine in Locally Available Sweet Supari Marketed in Karachi, Pakistan - Rehmani, Midhat; Raza, Rashid (Journal of Research (Science), 2025)
The frequency of use of betel nut has been increasing in the city of Karachi, Pakistan for decades and that use is more frequently associated with the chewing of tobacco. New generation has become addicted of using it creating doubts of contamination of addictive in the sweet supari sold in the city. In the present study different brands of sweet supari (chewing areca nut products) which were expected to contain addictive substances were analyzed to determine the levels of morphine. The samples of four different brands of sweet supari were randomly collected from different shops of Karachi, Pakistan. A total of 100 samples i.e. 30 samples of brand 1, 20 samples of each brand 2, brand 3 and brand 4 were taken for detection of opium. Samples were extracted by using standard method of extraction using methanol as an extracting solvent. The analysis of each sample for detection of opium was carried out by using standard methods of analysis by HPLC. The limit of detections (LODs, n=10) for the HPLC method were found to be 1.4ng/mL. It is glad to report that the level of morphine in all 100 samples of four various brands was detected less than the detection limit of HPLC. The results of the current study were very encouraging and inspiring that the sweet supari samples are not harmful and dangerous in terms of contamination of addictive. However, other adverse health effects of this silent killer should be taken into account on utilizing it.